Nyasha Harper-Michon, a constructive woman - United Nations Educational, Scientific; Cultural Organization; Anuliina Savolainen (The UNESCO Courier, 2024)
To be sustainable, a city of tomorrow must be more inclusive and accessible, says Nyasha Harper-Michon, an architect based in the Netherlands. She is striving to get the message across to the construction industry and young architects. Social media plays a key role in her strategy.